1988
DOI: 10.1042/bj2530073
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of diacylglycerol accumulation in response to vasopressin stimulation in hepatocytes of continuously endotoxaemic rats

Abstract: The content and composition of 1,2-diacyl-sn-glycerol (1,2-DAG) was determined in hepatocytes from saline (0.9 % NaCl)-and Escherichia coli endotoxin (ET)-infused rats upon continuous vasopressin (VP) (10-8 M) stimulation. In both experimental groups the accumulation of 1,2-DAG was detected after a lag period (2-5 min), was sustained up to the last time analysed (10 min), and C18 0-and C20 4-fatty-acid-containing-DAG accumulation preceded that of DAG containing other acyl groups. In hepatocytes from ET-infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…2-3 nmol of fatty acid/mg dry wt. of hepatocytes [38][39][40]. This rise occurs despite the presence of an important DAG kinase activity, which is also stimulated by VP, that may remove part of the DAG formed [41].…”
Section: Discussionmentioning
confidence: 99%
“…2-3 nmol of fatty acid/mg dry wt. of hepatocytes [38][39][40]. This rise occurs despite the presence of an important DAG kinase activity, which is also stimulated by VP, that may remove part of the DAG formed [41].…”
Section: Discussionmentioning
confidence: 99%
“…Work by others has shown that in various cell types the DAG generated after stimulation may originate from several sources (Pelech & Vance, 1989;Exton, 1990). For example, cell stimulation may result in parallel activation of both a PIC and a phosphatidylcholinespecific phospholipase C, the latter producing a greater and prolonged accumulation of DAGs with a composition different from the PPI-derived DAG (Rodriguez de Turco & Spitzer, 1988;Pessin & Raben, 1989). In addition, the PPIderived DAG may exert a positive feedback effect by stimulating PLC to generate additional DAG from several phosphoglycerides (Exton, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of 3-and 30-h time points for analysis enabled us to compare 02 generation by liver NPC during the early response to LPS with that during a later phase, when morbidity is maximal and metabolic responses are at their nadir (25,53,55,70).…”
Section: Discussionmentioning
confidence: 99%
“…At 3 h, rats do not show signs of morbidity, yet at the hepatic cellular level the vasopressin-stimulated inositol lipid-mediated signal transduction is already impaired (54). At the 30-h time point, maximal morbidity and severe impairment of hepatocyte and adipocyte responses are observed (14,53,55,71).…”
mentioning
confidence: 99%
See 1 more Smart Citation